SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170930-ms
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Modeling of Reaction-Induced Injectivity Alteration During CO2 Flooding in Carbonate Reservoirs

Abstract: Geochemical reactions between fluids and carbonate rocks can change porosity and permeability during CO 2 flooding, which may significantly impact well injectivity, well integrity, and oil recovery. Reactions can cause significant scaling in and around injection and production wells leading to high operating costs. Dissolution-induced well integrity issues and seabed subsidence have also been reported as a substantial problem at the Ekofisk field. Furthermore, mineral reactions can create fractures and vugs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…Natural analog studies, as well as experimental and modeling work have shown the potential of CO 2 migration into shallow aquifers (Carroll et al, 2014;Keating et al, 2013;Smith et al, 2013), which can result in groundwater acidification (Apps et al, 2010;Carroll et al, 2009), heavy metal mobilization (Frye et al, 2012;Lawter et al, 2015;Zheng et al, 2009), and mineral dissolution (Wang and Jaffe, 2004), all leading to detrimental impacts on water quality. The dissolution of CO 2 acidifies brines in deep saline aquifers, potentially dissolving solid material and increasing in situ permeability (Li et al, 2006;Qiao et al, 2015). These processes raise the risks of leakage through existing interfaces, fractures, and faults (Gaus, 2010;Keating et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Natural analog studies, as well as experimental and modeling work have shown the potential of CO 2 migration into shallow aquifers (Carroll et al, 2014;Keating et al, 2013;Smith et al, 2013), which can result in groundwater acidification (Apps et al, 2010;Carroll et al, 2009), heavy metal mobilization (Frye et al, 2012;Lawter et al, 2015;Zheng et al, 2009), and mineral dissolution (Wang and Jaffe, 2004), all leading to detrimental impacts on water quality. The dissolution of CO 2 acidifies brines in deep saline aquifers, potentially dissolving solid material and increasing in situ permeability (Li et al, 2006;Qiao et al, 2015). These processes raise the risks of leakage through existing interfaces, fractures, and faults (Gaus, 2010;Keating et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This compositional model can be used to simulate a variety of problems including the black oil model, EOS compositional model and reactive transport models (Qiao et al 2014;Qiao et al 2015). The set of partial differential equation (PDE) and local algebraic equations are solved together.…”
Section: Compositional Modelmentioning
confidence: 99%
“…RTMs have been utilized as integration and interpretation tools in a diverse array of subsurface environments involving porous and fractured media [ Li et al ., ; MacQuarrie and Mayer , ; Steefel et al ., ; Prommer et al , ]. RTMs have been applied to understand processes relevant to chemical weathering [ Bolton et al ., ; Brantley and Lebedeva , ; Maher et al ., ; Moore et al ., ], biogeochemical cycling in marine sediments [ Dale et al ., ; Krumins et al ., ; Regnier et al ., ], environmentally bioremediation [ Druhan et al ., ; Li et al ., ], natural attenuation [ Liu et al ., ; Mayer et al ., ], geological carbon sequestration [ Brunet et al ., ; Navarre‐Sitchler et al ., ; Xu et al ., ; Zhang et al ., ], nuclear waste storage [ Saunders and Toran , ; Soler and Mader , ], and energy production [ Audigane et al ., ; Qiao et al ., ]. RTM studies have so far mostly been applied at the spatial scales of pores at microns [ Fang et al ., ; Kang et al ., ; Li et al ., 2006, ; Molins et al ., ; Scheibe et al ., ], to columns at tens of centimeters [ Liu et al ., ; Salehikhoo and Li , ], and to field scales at tens of meters with the capability of explicitly taking into account subsurface spatial heterogeneity [ Bao et al ., ; Yabusaki et al ., ].…”
Section: Introductionmentioning
confidence: 99%